Pollen evidence of Late Holocene treeline fluctuation from the southern Coast Mountains, British Columbia - Evans, Martin (Géographie physique et Quaternaire, 1997)
Abstract Palynological records of Holocene climate change in the southern Coast Mountains identify the Neoglacial period, subsequent to 6 600 BP, as cooler and wetter than the preceding Hypsithermal. However, geomorphic evidence of alpine glacier advance suggests that there were three distinct cooler/wetter periods during the Neoglacial. By careful selection of a sensitive alpine site this study has enabled the recognition of two of these stages in a palynological record of Neoglacial climate. Pollen spectra, conifer needle macrofossils, organic matter content, and magnetic susceptibility were assessed for a continuous sequence of sediment from Blowdown Lake, which has a basal date older than 4 000 BP. Comparison of the Picea/Pinus pollen ratios from the core with modern surface samples suggests that treeline was at least 100 m above its present elevation until 3 400 BP, indicating that summer temperatures were at least 0.7 ° C above the present. Treeline declined to near present levels by around 2 400 BP. Two subsequent periods of lower treeline were identified which appear to correlate approximately with the Tiedemann and Late Neoglacial periods of glacier advance in southwestern British Columbia. Differences between Picea/Pinus and Abies/Pinus ratios from the core are consistent with the autecology of the species. This suggests that the sensitivity of the pollen ratio approach to reconstructing treeline is dependent on the ratios selected.